Sharia Incorporated. A Comparative Overview of the Legal Systems of Twelve Muslim Countries in Past and Present - Jan Michiel, Otto (Law, Governance, and Development, 2010)
This book is an ambitious study of how Islamic law traditions have been incorporated into the national legal systems throughout the Muslim world. Both puritan Islamists and Western alarmists tend to oversimplify and misrepresent the role and position of sharia. In response, this book takes stock of the actual legal positions, putting them into their socio-political and historical contexts. The twelve country chapters speak to the historical evolution of Islamic, legal, and political ideas and practices.